Factors influencing net income from a steer through feedlot - J.K. Blum; R.R. Schalles; K.O. Zoellner (Kansas Agricultural Experiment Station Research Reports, 1976)
Steers entering feedlots with higher starting weight per day of age had greater net value a t slaughter than lighter steers. Faster gaining steers brought the highest net income. Age on feed did not influence net income. High dressing percentage increased the net income but generally the relationship was low between carcass traits and net income.
Keywords: Cattlemen' s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Income; Steer; Feedlot; Carcass traits